TREATMENT OF DIABETIC FOOT ULCER USING MATHAN THYLAM DRESSING AND TRIPHALA CHOORANAM WASH- AN INEXPENSIVE YET EFFECTIVE TREATMENT. - Dr. Binthuja G Dharan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Diabetes presents as one of the basic threats to the people, as its complications extend to even neuropathies and osteomyelitis. 77 million Indians above 18 years of age suffer from Type II Diabetes Mellitus1. The mean period since diabetes onset to the development of Diabetic Neuropathy is usually around 8.3 years2. Diabetic foot ulcers develop mostly due to plantar pressure or small lesions that can occur due to some external object, disrupting the continuity in foot tissues. This is a case report that expresses the results of using Mathan Thylam- An Oil- based drug that is commonly used for the management of wounds in Siddha System of Medicine. This report shows the effect of the external drug on a patient who presented with a foot ulcer with poor clinical outcome. This treatment, if executed in patients with diabetic foot ulcers, could prove as a cost effective and efficient, yet easy procedure for the caretakers of the patients.